2011
DOI: 10.1016/j.jval.2011.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Toward Identifying the Causes and Combinations of Causes Increasing the Risks of Nonadherence to Medical Regimens: Combined Results of Two German Self-Report Surveys

Abstract: About one-third of patients can be classified as nonadherent. Intentional/medication-based NA causal factors explain the NA considerably better than do socioeconomics. The existence of more than one cause of risk considerably increases the NA risk of a patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
22
2
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 70 publications
0
22
2
5
Order By: Relevance
“…In order to improve adherence, it is necessary to understand the reasons behind NA. Previous studies have shown that adherence is affected by sociodemographic (eg, age and sex) and socioeconomic factors, the patient’s attitude towards drugs, their relationship with the health care professional, patient characteristics, the prescribing of complicated dosage regimens, and the development of adverse drug reactions (ADRs) 1,2,4,68. Moreover, psychological distress, such as anxiety and depression, which affect cognitive function and health behavior, also influence adherence 9.…”
Section: Introductionmentioning
confidence: 99%
“…In order to improve adherence, it is necessary to understand the reasons behind NA. Previous studies have shown that adherence is affected by sociodemographic (eg, age and sex) and socioeconomic factors, the patient’s attitude towards drugs, their relationship with the health care professional, patient characteristics, the prescribing of complicated dosage regimens, and the development of adverse drug reactions (ADRs) 1,2,4,68. Moreover, psychological distress, such as anxiety and depression, which affect cognitive function and health behavior, also influence adherence 9.…”
Section: Introductionmentioning
confidence: 99%
“…Overall, incomplete adherence has been found to occur in 26% to 60% of all patients 1315. For Germany, the results range between 35% and 50%,16,17 yet to this point, adherence has only been investigated in a few studies. In general, the findings vary depending on sample characteristics and applied measurement instruments 18,19.…”
Section: Introductionmentioning
confidence: 99%
“…Adherence measures include pill count, physical tests, medical records, self-report, collateral report, or electronic monitoring 12. Concerning sample characteristics, the following health-related variables have been found to be statistically significantly associated with incomplete adherence: disease (particularly low subjective severity of the disease to be treated, or low “disease threat”;12 also the occurrence of depression21); low objective severity of disease in patients with less serious conditions as well as a high objective severity of disease in patients with more serious conditions;22 low perceived need for medication;23 lack of social support (including emotional support, family cohesiveness, and marital status);24 poor communication between patient and physician;25 high complexity of a patient’s medication regimen;16,18,26 and low extent of medication information (in this context, medication information means the level to which patients feel they have received enough information about prescribed medication) 27,28. Unfortunately, these health-related factors are not always easy to assess in practice.…”
Section: Introductionmentioning
confidence: 99%
“…Such factors that lead to intentional behaviors are the cost of medication, presence of adverse effects, or a lack of understanding of the seriousness of the disease. The existence of one or more intentional, medication-based causal factors considerably increases the risk of patient nonadherence 15. Intentional barriers have been traditionally addressed through patient assistance or disease state management programs; however, little emphasis has been placed on methods to address unintentional barriers to patient adherence 16.…”
Section: Introductionmentioning
confidence: 99%